Effect of bionic coupling units׳ forms on wear resistance of gray cast iron under dry linear reciprocating sliding condition. (July 2015) - Pang, Zuobo; Zhou, Hong; Xie, Guofeng; Cong, Dalong; Meng, Chao; Ren, Luquan
Abstract: In order to get close to the wear form of guide rails, the homemade linear reciprocating wear testing machine was used for the wear test. In order to improve the wear-resistance of gray cast iron guide rail, bionic coupling units of different forms were manufactured by a laser. Wear behavior of gray-cast-iron with bionic-coupling units has been studied under dry sliding condition at room temperature using the wear testing machine. The wear resistance was evaluated by means of weight loss measurement and wear morphology. The results indicated that bionic coupling unit could improve the wear resistance of gray cast iron. The wear resistance of gray cast iron with reticulation bionic coupling unit is the best. When the load and speed changed, reticulation bionic coupling unit still has excellent performance in improving the wear resistance of gray cast iron. Highlights: Bionic coupling surface is beneficial to improve wear resistance of gray cast iron. The liner reciprocating behavior of bionic coupling samples was studied. The reticulation unit is the most effective to improve wear resistance.